Radionuclide techniques for the evaluation of renal function: advantages over conventional methodology - Bubeck, Bernd (Current opinion in nephrology and hypertension, 1995)
Aspirin renography, a new approach for the detection of renovascular hypertension, is described and compared with captopril scintigraphy. The behaviour of the new radiopharmaceutical 99mTc-ethylenedicysteine is examined for the first time in patients with impaired renal function and compared with 99mTc-mercaptoacetyltriglycine and with orthoiodohippurate. It is not yet possible to draw final conclusions about the advantages of aspirin renography and 99mTc-ethylenedicisteine over established methods and radiopharmaceuticals, respectively. In the diagnostic evaluation of renal transplants the degree of parenchymal retention is crucial. A newly described method for its quantitation is simpler and apparently more accurate than the excretion index frequently used.
Gesehen am 03.07.2024